Perlindungan Konsumen Atas Pemalsuan Nomor Rangka Motor dalam Transaksi Jual Beli Sepeda Motor Perspektif Fatwa MUI NO. 43/DSN-MUI/VIII/2004: Studi Kasus Desa Tanjung Sari, Kecamatan Batang Kuis - Randy Hardiansyah Sitepu; Rahmat Hidayat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines consumer protection against the practice of motorcycle chassis number forgery in used motorcycle sale and purchase transactions, with a case study conducted in Tanjung Sari Village, Batang Kuis District. The background of this research is based on the information asymmetry regarding the forgery of chassis numbers in motor vehicle transactions. This study aims to analyze the forms of legal protection available to consumers under Law Number 8 of 1999 concerning Consumer Protection and to examine the practice from the perspective of Islamic law based on DSN-MUI Fatwa No. 43/DSN-MUI/VIII/2004. This research employs an empirical juridical method with case, legal, and conceptual approaches. Data were collected through interviews, observations, and document studies, and were subsequently processed and analyzed using qualitative methods. The results indicate that the practice of chassis number forgery constitutes a violation of consumers’ rights due to the discrepancy between the actual condition and specifications of the goods sold, as well as the consumers’ right to compensation. This practice is inconsistent with Article 8 paragraph (1) letter f and Article 4 letter h of Law Number 8 of 1999 concerning Consumer Protection. From the perspective of DSN-MUI Fatwa No. 43/DSN-MUI/VIII/2004, this practice results in a real loss that renders the contract defective, thereby obligating the seller to provide ta’widh (compensation). Therefore, greater consumer awareness, stronger transaction verification systems, stricter law enforcement, and effective compensation mechanisms are necessary to ensure optimal consumer protection.